PENGARUH TERAPI PSIKODINAMIK TERHADAP PERUBAHAN STATUS MENTAL PASIEN SKIZOFRENIA YANG DIUKUR MENGGUNAKAN PANSS-EC DI RUMAH SAKIT JIWA ACEH - Denafianti Denafianti; Hady Maulanza (Jurnal Sains Riset, 2021)
The mental status of people with mental disorders, especially schizophrenia, is very different from the mental status of humans in general, schizophrenia can be suffered by anyone both in adolescents, adults and the elderly. Schizophrenia can be influenced by several factors, such as biological factors, genetic factors, psychological factors, behavioral responses, and social responses. Where schizophrenia is a disease that affects the brain and causes strange and disturbed thoughts, perceptions, emotions, movements, behaviors. One of the ways to handle mental status disorders in schizophrenic patients can be done through psychodynamic therapy in the form of therapy by speaking freely and openly which is carried out 3 times a week for 2 weeks. The purpose of this study was to analyze the effect of psychodynamic therapy on changes in mental status of schizophrenic patients at the Banda Aceh Mental Hospital 2018. The design in this study was a quasi-experimental study (quasi-experimental) which is a study by conducting experimental activities (experiments). The research design used was a non-equivalent (pretest and posttest) control group design which was divided into two groups, 15 intervention groups and 15 control groups. With the sampling process using purposive sampling. The data collection process was carried out for 16 days. Analysis using t-test. There is an effect of psychodynamic therapy on changes in mental status of schizophrenic patients at the Banda Aceh mental hospital with (p-value 0.000). Health workers, especially nurses for mental patients, need to do psychodynamic therapy to improve mental health status, especially in schizophrenia patients.Keywords: mental status, psychodynamic therapy, schizophrenic patients